(untitled) (Damascus University Journal of agriculture sciences, 2021)
In this study, the effects of different gibberellin concentrations and different treatment periods on the germination of potato tubers and the growth and yield of the resulting plants were investigated. The tubers were soaked in a 5, 10 and 20 ppm of water solution of gibberellin for 5, 10 and 20 minutes, then it were planted and the germination speed and percentage, the number of grown sprouts, the number of branches and leaves on the plant, the number of tubers on the plant, the weight of the tuber and yield were calculated. The treatments of tubers in general, and the treatment of 20 ppm of gibberellin for 20 minutes in particular, led to an increase in the speed and percentage of germination, the number of grown sprouts, the number of branches and leaves on plant, the number of tubers on plant and yield. This treatment can be adopted by farmers as an easy, efficient and inexpensive method to increase potato yield.